Indigenous knowledge on common medicinal plants among Raji Community of Surkhet district, mid-western Nepal - Thapa, Lal Bahadur (Nepalese Journal of Biosciences, 2013)
Rajis are one of the endangered indigenous tribe of Nepal distributed natively in Surkhet. In present situation the Rajis are in great pressure to change their ways of practice, belief, decision making and harvesting plant resources due to increasing population, migration and modernization. The present paper highlights the indigenous knowledge and practice of medicine preparation from common ten medicinal plants of their localities, transformation of the knowledge and response of respondents on conservation and management of medicinal plants. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7494 Nepalese Journal of Biosciences 2 : 88-92 (2012)